Cloistral scriptoria and medieval Cistercian legislation on the book - Marszalska, Jolanta M. (Saeculum Christianum. Pismo Historyczne, 2021)
The earliest books in the early Piast state in the second half of the 10th century were likely imported from the Benedictine scriptoria in Bavaria, Saxony, Rhineland, and Lorraine. These manuscripts contained Biblical texts and liturgical books indispensible for celebrating the Mass. The 12th-century precepts determining the establishment of new Cistercian cloisters necessitated the parent monastery to provide the monks delegated to the new coenobium with at least nine basic and indispensible books: the Missal, the Epistolary, the Gospels, the Gradual, the Antiphonary, the Hymnal, the Psalter, the Lectionary, and the Calendar. The said regulations rendered the work of copyists particularly important. One testament to the weight of the Cistercian cloister scribes was their exemption by the General Chapter from other monastic duties performed for their respective monasteries, coupled with dispensation from prescribed rest in favor of additional work (if so required). Apart from the reproduction of liturgical texts and memorative libri vivorum et mortuorum, the Cistercian scriptoria also saw the edition of the running administrative and economic records of a given monastery. Working in the silence of the scriptorium, monks would edit the cloistral yearbooks, obituaries, monastery chronicles, and rhymed epitaphs. They contained notes of daily life outside the enclosure, the names and functions of individual friars, notes of watershed events taking place away from the monastery, and mentions of natural disasters (floods, fires, epidemics) in the surrounding areas, along with the incurred losses. The surviving monastery chronicles provide invaluable insight to the sensibilities and interpersonal relations of cloistered communities, as well as their relations with the immediate surroundings, and manifestations of medieval worldviews.